Tax arrears and causes of arrears (Eurasian Research Bulletin, 2024)
In this article, improvement of the mechanism of tax collection, improvement of service and education of taxpayers, simplification of the tax system and procedures, development of effective communication channels between taxpayers and tax authorities, improvement of mechanisms of tax collection. In addition, the theoretical and practical aspects of the formation of trust and perception of justice and the use of effective coercive measures increase compliance, the trends in the development of relations, and the main reasons for the occurrence of tax arrears in terms of taxes and fees.